2019
DOI: 10.1108/aia-09-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in spontaneously performing level 2 perspective-taking skills in children with autism spectrum disorder

Abstract: Purpose The purpose of this paper is to investigate why children with autism spectrum disorder (ASD) tend to respond to tasks from their own perspective. The authors investigated the effects of explicitness of viewpoint on performance of spontaneous level 2 perspective-taking skills in six- to eight-year-old children with ASD. Design/methodology/approach The authors conducted visual perspective-taking tasks with explicit and implicit instructions about the viewpoint to be used. Participants operated a toy ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
9
2
Order By: Relevance
“…This method requires that the distance between the participant's head and the eye tracker be kept somewhat constant. In VPT2, the sensation and minute movement of the body is in an unstable position (Watanabe, 2016), and physically turning or moving the body to another viewpoint (Asaoka et al, 2019;Kessler & Thomson, 2010) affects performance. Thus, VPT2 is very sensitive to body sensation and position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method requires that the distance between the participant's head and the eye tracker be kept somewhat constant. In VPT2, the sensation and minute movement of the body is in an unstable position (Watanabe, 2016), and physically turning or moving the body to another viewpoint (Asaoka et al, 2019;Kessler & Thomson, 2010) affects performance. Thus, VPT2 is very sensitive to body sensation and position.…”
Section: Discussionmentioning
confidence: 99%
“…In the ASD group, children with ASD who met the following criteria were newly recruited: 1) the CA is 8 years old. The reason for this was that the children after the age of 8 years are able to perform VPT2 skills spontaneously (Asaoka et al, 2019) and their fluency increased (Elekes, Varga, & Király, 2017), suggesting that the introduction of conditions was expected to be effective; 2) intellectual development is more advanced. All children were assessed for intellectual development with the Picture Vocabulary Test-Revised (PVT-R) (Ueno, Nadeo, & Iinaga, 2008), which is the official standardized scale in Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies involving patients with social function impairments also support this dual‐process view of VPT. Patients with schizophrenia or autism spectrum disorder (ASD) show more severe damage in spontaneous VPT than intentional VPT (Asaoka, Takahashi, Chen, Fujiwara, Watanabe, & Noro, 2019; Eack, Wojtalik, Newhill, Keshavan & Phillips, 2013; Hamilton, Brindley & Frith, 2009; Kronbichler, Stelzig‐Scholer, Pearce et al ., 2019). For instance, Doi, Kanai, Tsumura, Shinohara & Kato (2020) found that male adults with ASD showed a deficiency in spontaneously taking others’ perspectives in the dot perspective task, which was manifested by a reduction in allocentric interference.…”
Section: Introductionmentioning
confidence: 99%
“…Level-2 VPT contributes more to effective social interaction than level-1 VPT. Several studies have suggested that a deficiency in level-2 VPT is common in children with ASD, while level-1 VPT is intact (Asaoka et al, 2019;Hamilton et al, 2009). Asaoka et al (2019) found that 6-to 8-year-old children with ASD only showed a weak tendency to spontaneously use level-2 perspective-taking skills.…”
Section: Introductionmentioning
confidence: 99%